ChemInform Abstract: Synthesis of Trifluoromethylated [1, 4]Diazepines from 1, 1, 1‐Trifluoroalk‐3‐yn‐2‐ones. Issue 11 (March 2015) - Romanov, Alexey R.; Rulev, Alexander Yu.; Ushakov, Igor A.; Muzalevskiy, Vasiliy M.; Nenajdenko, Valentine G.
Abstract The target heterocycles are formed under mild conditions in good yields and with high selectivity.